2011
DOI: 10.1371/journal.pntd.0001137
|View full text |Cite
|
Sign up to set email alerts
|

Tacaribe Virus but Not Junin Virus Infection Induces Cytokine Release from Primary Human Monocytes and Macrophages

Abstract: The mechanisms underlying the development of disease during arenavirus infection are poorly understood. However, common to all hemorrhagic fever diseases is the involvement of macrophages as primary target cells, suggesting that the immune response in these cells may be of paramount importance during infection. Thus, in order to identify features of the immune response that contribute to arenavirus pathogenesis, we have examined the growth kinetics and cytokine profiles of two closely related New World arenavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 43 publications
5
60
2
2
Order By: Relevance
“…Several lines of evidence suggested that TCRV might be impaired in its ability to suppress apoptosis induction compared with JUNV (Groseth et al, 2011;Wolff et al, 2013a), leading us to investigate whether TCRV infection indeed induces appreciable levels of apoptosis in infected cells, and, if so, by what mechanisms. Vero E6 cells, which represent a highly permissive system for arenavirus infection and are defective in IFN secretion, were inoculated with TCRV at an m.o.i.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several lines of evidence suggested that TCRV might be impaired in its ability to suppress apoptosis induction compared with JUNV (Groseth et al, 2011;Wolff et al, 2013a), leading us to investigate whether TCRV infection indeed induces appreciable levels of apoptosis in infected cells, and, if so, by what mechanisms. Vero E6 cells, which represent a highly permissive system for arenavirus infection and are defective in IFN secretion, were inoculated with TCRV at an m.o.i.…”
Section: Resultsmentioning
confidence: 99%
“…Stock preparations of TCRV with a titre of 1.5|10 6 p.f.u. ml 21 were inactivated as previously described (Carter et al, 1973;Elliott et al, 1982;Groseth et al, 2011) by irradiation at 254 nm using a UV lamp (CAMAG) for 1 h. Inactivated samples were analysed by plaque assay as described previously (Wolff et al, 2013a), to ensure complete inactivation (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…вирусы ласса и мопейя способны инфициро-вать первичные макрофаги человека и дендритные клетки, но патогенный для человека вирус ласса не активирует эти клетки в процессе инфицирования, а непатогенный вирус мопейя активирует эти клет-ки, что проявляется в повышении уровня экспрес-сии маркеров сD86, сD80 и α-интерферона [17]. аналогичным образом первичные макрофаги чело-века показывают более высокий уровень продукции интерлейкина-6, интерлейкина-10 и α-интерферона при инфицировании вирусом такарибе по сравнению с инфицированием патогенным для человека вирусом хунин [7]. показано, что Z-белок всех известных па-тогенных аренавирусов, в отличие от непатогенных, способен ингибировать активацию макрофагов [27].…”
unclassified